2014
DOI: 10.14419/ijac.v2i2.2661
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer potential of various substituted pyridazines and related compounds

Abstract: Pyridazine nucleus exhibited immense pharmacological activities. Pyridazine nucleus is present in various compounds that possess remarkable pharmacological activities. Various pyridazinone compounds have antitumor activity. Some of them pyridazinone derivatives bearing different moieties were exhibited excellent anticancer activity toward human cancer cell lines. They showed remarkable activity against leukemia, non-small cell lung cancer, colon, central nervous system, melanoma, ovarian and breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Pyridazine-based frameworks are widely distributed in biologically active products with anti-viral [ 15 , 16 , 17 , 18 , 19 , 20 ], anti-inflammatory [ 21 , 22 , 23 , 24 , 25 ], anti-microbial [ 26 , 27 , 28 ], anti-cancer [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], anti-convulsant [ 37 , 38 , 39 , 40 ], anti-analgesic [ 41 , 42 ], anti-tubercular [ 43 , 44 , 45 ], anti-hypertensive [ 3 , 46 ], anti-diabetic [ 47 ], anti-depressant [ 48 , 49 ], anti-Alzheimer’s [ 50 , 51 ], phosphodiesterase [ 52 , 53 ], platelet aggregation [ 54 , 55 , 56 , 57 ], and cholesterol acyl transferase inhibitor properties [ 58 ]. Peptide nucleic acids (PNAs) with new pyridazine-type nucleobases were reported as replacements for the DNA duplex bases instead of thymine, adenine, guanine and cytosine to form novel DNA or RNA duplexes [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyridazine-based frameworks are widely distributed in biologically active products with anti-viral [ 15 , 16 , 17 , 18 , 19 , 20 ], anti-inflammatory [ 21 , 22 , 23 , 24 , 25 ], anti-microbial [ 26 , 27 , 28 ], anti-cancer [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], anti-convulsant [ 37 , 38 , 39 , 40 ], anti-analgesic [ 41 , 42 ], anti-tubercular [ 43 , 44 , 45 ], anti-hypertensive [ 3 , 46 ], anti-diabetic [ 47 ], anti-depressant [ 48 , 49 ], anti-Alzheimer’s [ 50 , 51 ], phosphodiesterase [ 52 , 53 ], platelet aggregation [ 54 , 55 , 56 , 57 ], and cholesterol acyl transferase inhibitor properties [ 58 ]. Peptide nucleic acids (PNAs) with new pyridazine-type nucleobases were reported as replacements for the DNA duplex bases instead of thymine, adenine, guanine and cytosine to form novel DNA or RNA duplexes [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyridazinone derivatives have gained substantial attention within the field of medicinal chemistry. Pyridazine moiety has been tested extensively for its diverse biological activities including antiinflammatory, analgesic, anticancer, antiviral, antimicrobial, cardiovascular, antitubercular, antiobesity, antidiabetic, neuroprotective, and various other activities [90][91][92][93][94][95][96]. Cardiovascular diseases (CVDs) are the leading reason for death worldwide and remain the leading reason for avoidable death worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that some pyridazin-3(2h)-one derivatives specifically interact with and inhibit PIM (potential tumor targets) kinases with low nanomolar potency [18][19][20][21]. In addition, pyridazin-3(2h)-ones are endowed by many biological activities [22][23][24]. In this context, the present study was aimed at synthesizing new pyridazin-3(2h)-one derivatives with cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%